PELAKSANAAN PERJANJIAN SURAT PEMESANAN TOKO ANTARA PIHAK PEMESAN DENGAN PT. MAKMUR PAPAN PERMATA DI SUKARAMAI TRADE CENTER PEKANBARU - Dahnil, Silmia; Ismi, Hayatul; Dasrol, Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In accordance with the agreement made by PT. Makmur Papan Permata with traders / buyers ofshop units where when the building construction has been completed, handover will be carried out,handover is carried out on condition that the merchants who have made an order at that time must makepayment for the purchase, with 30% dp and continued payment of 70 % that can be done by repayment, instages or by entering into a credit agreement. The agreement went on as it should until a force majeure tookplace, namely a fire in 2015. Then PT. Makmur Papan Permata formed an addendum to the agreement thathad lasted so far with the merchant / owner of the store unit that ended up when the force majors took place.The purpose of this thesis is; First, to find out the implementation of the agreement between the rightsholder and PT. Makmur Papan Permata at Sukaramai Trade Center Pekanbaru. Second, to find out theobstacles of implementing the agreement PT. Makmur Papan Permata at Sukaramai Trade CenterPekanbaru.This type of research is sociological, because in this study the authors directly conducted research atthe location under study, in order to provide a complete picture of the problem under study. This researchwas conducted in the Pekanbaru area precisely at PT. Papan Makmur Permata on Sisingamangaraja Street,while the population and sample are all parties related to the problems examined in this study, the datasources used are primary data and secondary data, data collection techniques in this study withquestionnaires, interviews, and literature review.From the results of the study there were two main points that were concluded; First, PT. MakmurPapan Permata has done a default in the form of not fulfilling or carrying out the achievements as specifiedin the store order letter. Second, the obstacles in implementing the agreement of PT. Makmur PapanPermata in the Sukaramai Trade Center Pekanbaru is a factor in the delay in the handing over of the storeunits due to internal and external factors that are sufficiently hampering the smooth implementation of thedevelopment process in a timely manner. Author's Suggestions, First, In the implementation of theAgreement of Booking between the Buyer and PT. Makmur Papan Permata at the Sukaramai Trade CenterPekanbaru still lacks good communication between parties. Second, so that the buyer of the store is notdisadvantaged in the implementation of the agreement. Makmur Papan is related to the responsibility forcarrying out the Order Agreement.Keywords: Implementation of the Agreement, Force Major, Default.